The power of social media to influence people in Indonesia: case study of crazy rich scam and big data of election postponement - Garcia Krisnando Nathanael; Devi Angeliawati; Muhadjir Muhadjir (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to explain the power of social media to influence people in Indonesia with the fraud case carried out by crazy rich Doni Salmanan and Indra Kenz, as well as the Big Data claim case which shows the postponement of the 2024 election. Social media has become a new medium for interaction, so that many parties who use social media ranging from individuals, influencers, business people, companies to government agencies to share activities, information, promotions and even show off their wealth and luxurious lifestyle. The concepts used in this study include Big Data and Flexing as an analytical instrument for the phenomena in this study. Researchers used qualitative methods using secondary data. The results of this study indicate that there is a common thread between social media, flexing carried out by crazy rich Doni Salmanan and Indra Kenz, and Big Data regarding the postponement of the 2021 elections where social media has strong power to influence and control public opinion in Indonesia.